Qualitative (pure) mathematics as an alternative to measurement - Linkov, Václav (Frontiers in Psychology, 2024)
This paper focuses on the possible usage of qualitative mathematics in psychology. Qualitative mathematics is understood to be equivalent to pure mathematics. First, it is explained that mathematics is a discipline studying patterns in reproducible mental objects. Qualitative mathematics is presented as an alternative to measurement, potentially offering the same level of exactness, clarity, and rigor. This perspective might lead psychologists to explore connections between a phenomenon and any kind of mathematical structure, regardless of whether the structure is quantitative. Usage of (any) mathematical structures might require scholars who are familiar with them. Consequently, changes in mathematics education may also be needed. Introducing nonnumerical structures into mathematics education-thereby partially revisiting the New Math Movement-could train individuals more prepared for a creative approach to the use of structures and less inclined to view everything as quantitative.